Simulation of a cyber-physical manufacturing system - Liu, Jiayao (2017)
In this paper, we will implement a timed supervisory control strategy in a simulated manufacturing system developed with libFAUDES. In order to generate a time optimal supervisor, we will construct the time-weighted models of the system and specify the imposed requirements. In the meantime, basic concepts of languages and automata will be introduced as fundamental theories. Then, a simulated cluster tool system will be displayed as an example of a discrete event system to verify the time optimal control strategy. We could directly evaluate the performance of the supervisor through the simulation result and analyze the advantage and potential weakness.